Millenarian religion and radical politics in Britain 1815-1835: a study of Southcottians after Southcott - Lockley, P (2009)
The popular millenarian movement founded by Joanna Southcott (1750-1814) enjoyed a complex relationship with political radicalism in early nineteenth-century Britain. Southcott opposed radicalism during her lifetime, encouraging her followers to await a messianic agent of the millennium. Within two decades of the prophet’s death – as Southcott expected to give birth to this messiah – some surviving Southcottians became political radicals, most notably, John ‘Zion’ Ward (1781-1837) and James Elishama Smith (1801-57). Ward was a popular preacher during the agitations around the Reform Bill, Smith a radical lecturer, editor of Robert Owen’s journal Crisis, and ideologue within general trades unionism in 1833-34. The respective influence of each figure drew several hundred Southcottians into engagement with politics. This thesis presents a new interpretation of why such millenarians engaged with radicalism. Utilising a substantial range of Southcottian and radical sources, many previously unstudied, it challenges the existing explanations of Southcottian radicalism of E.P. Thompson, J.F.C. Harrison, Barbara Taylor and others. Through a close study of the religious experience, ideas and practices of Southcottians in 1815-35, it locates an altered disposition towards social activity through the evolving millennial theologies of Southcottian groups and the personal acquaintanceship of individual believers with radical freethinkers. Under the prophetic leadership of Zion Ward and John Wroe (1782-1863), earlier Southcottian notions of the respective roles of divine and human agency in the realising of the millennium were changed by 1830. This led Southcottians to a new sense of agency, where their own actions took on a millennial significance when directed towards the achievement of God’s perceived intentions for the world. For some, this presented engagement with political radicalism, even freethought radicalism, in a new light: as action apposite to their beliefs. This argument features an alternative theoretical framework for millenarian beliefs which takes account of the way conceptions of human agency can vary within religious movements centred on modern prophecy. In exposing the inadequacy of existing pre- and postmillennial categories to explain such beliefs, it demonstrates how visionary religion can inspire expectations of both disruptive and evolutionary change, and require both divine and human agency, in the realisation of the millennium. This is a study in religious history, orientated towards politics. It demonstrates that a sensitivity to how visionary religious ideas influenced individuals involved in political movements, aids an improved understanding of political motivations and ideals.